2017
DOI: 10.14419/ijm.v5i2.8315
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the toxic influence of vitamin E (dl-alpha-tocopheryl acetate) and treatment with aqueous extracts of cinnamon or anise on lipid profile and liver functions of female wistar rats

Abstract: The toxic effects of vitamin E and its treatment with aqueous extracts of Cinnamon or anise on lipid profile and liver functions of female wistar rats were examined for six weeks during September 2016 at labs in al-Neelain University. 18 rats were divided into six groups: 1. negative control group (sunflower oil), 2. Positive control group and rest groups given (1500 mg/Kg/BW/day of Vitamin E). After two hours, the four treated groups received a low dose (2.13g/Kg) and a high dose (3.20g/Kg) 20g/Kg from Cinnam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…(Nair et al, 2018) cleared that Pimpinella anisum L. have the ability to contribute to protection against renal failure by improving the structure of glomeruli and kidney tubules in the anisetreated group. ( Ibrahim, 2017( found that anise seeds have an improving effect on the functions of kidney enzymes, especially urea. This in agreement with our current study, the group treated with anise powder biscuits had a significant reduction in the level of urea compared to the control group at P< 0.05.…”
Section: Effect Of Feeding On Biscuits Supplemented With Cinnamon Fen...mentioning
confidence: 99%
See 1 more Smart Citation
“…(Nair et al, 2018) cleared that Pimpinella anisum L. have the ability to contribute to protection against renal failure by improving the structure of glomeruli and kidney tubules in the anisetreated group. ( Ibrahim, 2017( found that anise seeds have an improving effect on the functions of kidney enzymes, especially urea. This in agreement with our current study, the group treated with anise powder biscuits had a significant reduction in the level of urea compared to the control group at P< 0.05.…”
Section: Effect Of Feeding On Biscuits Supplemented With Cinnamon Fen...mentioning
confidence: 99%
“…(Wu et al, 2018) showed that combined treatment with cinnamaldehyde and PTH enhances osteoblasts in a rat model of osteoporosis. (Ibrahim, 2017), reported that cinnamon extract helps increase sex hormones, including testosterone and improves testosterone level. (Azam et al, 2017) found that administering different concentrations of fennel seeds significantly increased the levels of estrogen and progesterone hormones in the blood of adult female rats.…”
Section: Serum Hormones Of Aged Rats Fed On Biscuits Supplemented Wit...mentioning
confidence: 99%